French colonialism unmasked : the Vichy years in French West Africa - Ginio, Ruth, 1966- (France overseas., 2006)
Before the Vichy regime, there was ostensibly only one France and one form of colonialism for French West Africa (FWA). World War II and the division of France into two ideological camps, each asking for legitimacy from the colonized, opened for Africans numerous unprecedented options. French Colonialism Unmasked analyzes three dramatic years in the history of FWA, from 1940 to 1943, in which the Vichy regime tried to impose the ideology of the National Revolution in the region. Ruth Ginio shows how this was a watershed period in the history of the region by providing an in-depth examination of the Vichy colonial visions and practices in fwa. She describes the intriguing encounters between the colonial regime and African society along with the responses of different sectors in the African population to the Vichy policy. Although French Colonialism Unmasked focuses on one region within the French Empire, it has relevance to French colonial history in general by providing one of the missing pieces in research on Vichy colonialism. Ruth Ginio is a research fellow at the Harry S. Truman Research Institute for the Advancement of Peace in the Hebrew University of Jerusalem. She is the author of articles in International Journal of African Historical Studies, Revue d'histoire moderne et contemporaine, Cahiers d'etudes africaines, and several other journals